Legal shortcomings in multisectoral forums responding to child sexual abuse (CSA): lessons from a Zimbabwe case study - Muridzo, Noel G.; Mahunste, Samuel L.; Chikadzi, Victor; Mafa, Itai (National Association of Social Workers, 2021)
Legal services constitute an important component of the Victim Friendly System (VFS) in Zimbabwe, a multisectoral forum that offers distinct but complimentary medical, psychosocial and legal services to child sexual abuse (CSA) survivors. The paper identifies a number of loopholes in the VFS judicial services. A qualitative approach was adopted with data collected from 38 participants and 4 key informants selected using theoretical and purposive sampling respectively. A total of 300 court transcripts of child sexual abuse cases were also reviewed. Findings show that there exist legal shortcomings that include contradictions; the system permitting witness interference; the system suffers limited coverage and that the system releases offenders on bail into the child’s environment. We argue that these shortfalls are to the detriment of survivors’ wellbeing. These findings provide some insights that are useful in improving child protection interventions. Given the well documented effects of CSA on survivors and the importance of legal systems in child protection, we recommend legal and policy reforms in line with international conventions. In addition, there is need to increase access of services including judicial services.